THE POSSIBILITIES OF USING INFORMATION TECHNOLOGY IN MANAGEMENT OF THE ORGANIZATION'S PROCESSES OF EMERGENCY MEDICAL CARE - K.M. KOROTKOVA; A.V. SHULMIN (Avicenna Tajik State Medical University, 2018)
Objective: Improvement of the model of the automated control system to support the decision-making in the field of emergency medical care to the population of a large industrial center. Methods: The analysis of the activity of the ambulance station was studied the existing normative legal acts regulating the activity of emergency medical aid. A detailed study of software KGBUZ «KSSMP» - an automated control system (ASU) «MISS 03», working system of dispatching of vehicles - «AutoGRAPH». To create a model of its own software, the C++ programming language was used. Results: The model of the AnScor+ software and hardware complex created by us is organized as a distributed client-server system. The end devices are data collection terminals (mobile phones of ambulance crews running the Android operating system); a client-server Android application was developed for them. The interaction between mobile terminals, dispatcher terminals, and the MISS-03 automated control system is carried out centrally through the software of the AnScor+ server. Conclusion: The creation of such analytical services to ensure the solutions of the problems of transport logistics, automated patient flow management will allow realizing in practice the advanced algorithms of the medical emergency services, significantly improve the main performance indicators, such as the promptness of quality and the volume of medical care.